EFEKTIFITAS MEDIA SOSIAL SEBAGAI WADAH BERBAGI PENGETAHUAN PADA LINTAS GENERASI - Rindang Matoati; Ignatius Hari Santoso (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2020)
The purpose of this study is to find out the difference of effectivity of social media as a space to knowledge sharing between X, milenial and Z Generation. Sample used in this research is 60 respondents, which is from 20 X generation, 20 Milenial Generation and 20 Z generation in Semarang. This research  is using Kruskal Wallis method analysis with significany level 0,05.  The results showed that there is significant differences between X, Milenial, and Z generation to using social media as knowledge sharing media